Composite negative electrode for sodium battery and preparation method of composite negative electrode
By bonding the fluorine-containing polymer film to the surface of the sodium sheet of the sodium battery and forming a sodium fluoride layer, the problems of uneven deposition of sodium metal negative electrodes and SEI generation are solved, and the cyclic voltage stability and Coulomb efficiency of the sodium battery are improved.
Patent Information
- Application Number
- CN202311366368.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-19
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2043-10-19
AI Technical Summary
The sodium metal negative electrode has uneven deposition, high reactivity, and reaction with organic electrolytes to form an unstable solid electrolyte membrane (SEI), resulting in sodium dendrites growth and affecting battery stability and capacity.
The fluorine-containing polymer film is attached to the surface of the sodium sheet, and the sodium fluoride layer is catalyzed in the organic solvent to induce uniform deposition of lithium sodium ions and inhibit the growth of sodium dendrites.
By forming a sodium fluoride layer, it blocks the corrosion of the sodium metal sheet by water, inhibits the generation of SEI, improves the cyclic voltage stability and Coulomb efficiency of the sodium battery, and extends the battery life.
Smart Images

Figure CN119864368A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium battery materials, and in particular to a composite negative electrode for a sodium battery and a preparation method thereof. Background Art
[0002] Since lithium secondary batteries are constrained by resource scarcity, the task of finding alternative products is urgent. Compared with lithium, sodium has similar chemical properties, more abundant reserves, higher safety and high and low temperature performance, which makes the commercialization of sodium batteries very attractive. Among them, the sodium metal negative electrode is considered to be the "holy grail" electrode in sodium-ion batteries because of its lower potential of -2.71V relative to the standard hydrogen electrode and high specific capacity of 1166mAh / g.
[0003] However, there are still many problems with the sodium metal negative electrode. The uneven deposition of sodium ions and the highly reactive sodium will react with the organic electrolyte to form an unstable solid electrolyte membrane (SEI), leading to the growth of sodium dendrites. The continuous growth of sodium dendrites during the cycle will greatly affect the stability of the battery, causing battery failure and other problems. The loss of electrochemical activity of sodium will lead to battery capacity loss. The large-scale application of sodium metal batteries still faces severe challenges.
[0004] Therefore, constructing a more stable sodium metal anode and regulating the composition of the SEI film to inhibit dendrite growth are crucial to prolonging the life of sodium batteries. Summary of the invention
[0005] The purpose of the present invention is to provide a composite negative electrode for a sodium battery and a preparation method thereof. By pressing a fluorine-containing high molecular polymer film attached to the surface of metallic sodium and introducing an organic solvent to accelerate the defluorination reaction of the polymer film, a sodium fluoride / carbon interface layer is generated on the surface of the metallic sodium sheet, which can induce uniform deposition of lithium and sodium ions, effectively inhibit the growth of sodium dendrites during the charge and discharge process, and enable the sodium battery to have a more stable cycle voltage and a better battery cycle life.
[0006] To this end, in a first aspect, an embodiment of the present invention provides a composite negative electrode for a sodium battery, the composite negative electrode comprising: a sodium sheet, a sodium fluoride layer formed in situ on the surface of the sodium sheet, and a fluorine-containing polymer film;
[0007] The sodium fluoride layer is formed by reacting a sodium sheet having a fluorine-containing polymer film attached to its surface under the catalysis of an organic solvent;
[0008] The organic solvent includes esters and / or ethers.
[0009] Preferably, the thickness of the fluorine-containing polymer film is 0.01mm-0.2mm; the fluorine-containing polymer in the fluorine-containing polymer film includes: one or more of polytetrafluoroethylene (PTFE), polychlorotrifluoroethylene (PCTFE), perfluoroalkoxy resin (PFA), polyperfluoroethylene propylene (FEP), ethylene-tetrafluoroethylene copolymer (ETFE), and polyvinyl fluoride (PVF).
[0010] Preferably, the thickness of the sodium sheet is 0.1 mm-1 mm;
[0011] The organic solvent includes: one or more of diethylene glycol, triethylene glycol di-2-ethylhexanoate, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, and dioxolane.
[0012] Preferably, the thickness of the sodium fluoride layer is 1 μm-50 μm.
[0013] In a second aspect, an embodiment of the present invention provides a method for preparing the composite negative electrode according to the first aspect, the preparation method comprising:
[0014] The bulk sodium metal was cut into small pieces in a glove box filled with argon, rolled and then cut into sodium sheets;
[0015] In a glove box, a fluorine-containing polymer film is placed on the surface of a sodium sheet, and the fluorine-containing polymer film is adhered to the surface of the sodium sheet by applying pressure to obtain a prefabricated negative electrode;
[0016] The prefabricated negative electrode is immersed in an organic solvent to make the sodium in the sodium sheet react with the fluorine in the fluorine-containing high molecular polymer film to form a sodium fluoride layer, thereby obtaining a composite negative electrode.
[0017] Preferably, the thickness of the fluorine-containing polymer film is 0.01 mm-0.2 mm; the fluorine-containing polymer in the fluorine-containing polymer film includes one or more of polytetrafluoroethylene (PTFE), polychlorotrifluoroethylene (PCTFE), perfluoroalkoxy resin (PFA), polyperfluoroethylene propylene (FEP), ethylene-tetrafluoroethylene copolymer (ETFE), and polyvinyl fluoride (PVF);
[0018] The thickness of the sodium sheet is 0.1mm-1mm;
[0019] The organic solvent includes esters and / or ethers.
[0020] Preferably, the organic solvent includes: one or more of diethylene glycol, triethylene glycol di-2-ethylhexanoate, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, and dioxolane. Preferably, the soaking time is 1 minute to 10 minutes.
[0021] In a third aspect, an embodiment of the present invention provides a sodium battery, comprising a positive electrode, the composite negative electrode described in the first aspect, an electrolyte or a solid electrolyte, and a separator.
[0022] Preferably, the sodium battery comprises any one of a sodium ion battery, a sodium metal battery, and an all-solid-state sodium battery.
[0023] The embodiment of the present invention provides a method for preparing a composite negative electrode for a sodium battery. First, a layer of fluorine-containing high molecular polymer film is attached to the surface of a sodium sheet. Then, under the catalysis of a solvent, the sodium element in the sodium sheet reacts with the fluorine element in the polymer film more quickly to form a sodium fluoride layer, and finally a composite negative electrode is obtained. The preparation method is simple to operate, low in cost, and can be applied to large-scale batch production.
[0024] The composite negative electrode prepared by the above-mentioned preparation method in the embodiment of the present invention is applied to a sodium battery. During the battery cycle, the sodium fluoride layer in the composite negative electrode can effectively block the corrosion of water on the sodium metal sheet, and at the same time can inhibit the reaction of sodium with an organic electrolyte to generate an unstable solid electrolyte membrane (SEI) to cause the growth of sodium dendrites, thereby reducing the capacity loss of the battery and improving the stability and safety of the sodium battery. The present invention can adjust the thickness of the sodium fluoride layer by changing the thickness of the fluorine-containing high molecular polymer film, thereby improving the deposition of sodium, generating a stable SEI film, and realizing the rapid transfer and uniform deposition of sodium ions. The composite negative electrode has a more stable cycle voltage, so that the sodium battery has better coulomb efficiency and cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] The technical solution of the embodiment of the present invention is further described in detail below through the drawings and examples.
[0026] Figure 1 It is a flow chart of the method for preparing the composite negative electrode provided in an embodiment of the present invention. DETAILED DESCRIPTION
[0027] The present invention is further described in detail below through the accompanying drawings and specific embodiments, but it should be understood that these embodiments are only used for more detailed description and should not be understood as limiting the present invention in any form, that is, they are not intended to limit the protection scope of the present invention.
[0028] An embodiment of the present invention provides a composite negative electrode for a sodium battery, comprising: a sodium sheet, a sodium fluoride layer formed in situ on the surface of the sodium sheet, and a fluorine-containing high molecular polymer film; wherein the sodium fluoride layer is formed by reacting the sodium sheet with the fluorine-containing high molecular polymer film attached to the surface under the catalysis of an organic solvent.
[0029] The organic solvent specifically includes: one or more of diethylene glycol, triethylene glycol di-2-ethylhexanoate, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, and dioxolane.
[0030] The organic solvent used in the present invention has H n COC n H (n ≥ 1) structure, which can quickly remove sodium atoms from the metal lattice to form an O-Na-O structure. The fluoride ions in the fluorine-containing polymer film have strong adsorption and combine with the sodium in the O-Na-O structure to form NaF.
[0031] The thickness of the above-mentioned fluorine-containing polymer film is 0.01mm-0.2mm; the fluorine-containing polymer in the fluorine-containing polymer film includes: one or more of polytetrafluoroethylene (PTFE), polychlorotrifluoroethylene (PCTFE), perfluoroalkoxy resin (PFA), polyperfluoroethylene propylene (FEP), ethylene-tetrafluoroethylene copolymer (ETFE), and polyvinyl fluoride (PVF).
[0032] The sodium sheet is a sodium metal sheet with a thickness of 0.1 mm to 1 mm; the thickness of the sodium fluoride layer is 1 μm to 50 μm, preferably 20 μm.
[0033] The present invention provides a method for preparing the composite negative electrode. Figure 1 As shown, the specific steps include:
[0034] Step 110, cutting the bulk sodium metal into small pieces in a glove box filled with argon, rolling and then cutting into sodium sheets;
[0035] Among them, the bulk metallic sodium is stored in kerosene to avoid oxidation; the thickness of the cut sodium sheets is between 0.1mm and 1mm.
[0036] Step 120, placing a fluorine-containing polymer film on the surface of the sodium sheet in a glove box, and applying pressure to make the fluorine-containing polymer film adhere to the surface of the sodium sheet to obtain a prefabricated negative electrode;
[0037] The thickness of the fluorine-containing polymer film is 0.01 mm to 0.2 mm; the fluorine-containing polymer in the fluorine-containing polymer film includes one or more of polytetrafluoroethylene (PTFE), polychlorotrifluoroethylene (PCTFE), perfluoroalkoxy resin (PFA), polyperfluoroethylene propylene (FEP), ethylene-tetrafluoroethylene copolymer (ETFE), and polyvinyl fluoride (PVF);
[0038] The pressure can be applied manually or by using a tablet press or other equipment, as long as the fluorine-containing polymer film is attached to the surface of the sodium sheet.
[0039] Step 130, immersing the prefabricated negative electrode in an organic solvent, so that the sodium in the sodium sheet reacts with the fluorine in the fluorine-containing high molecular polymer film to form a sodium fluoride layer, thereby obtaining a composite negative electrode.
[0040] The organic solvent includes esters and / or ethers, specifically including one or more of ethylene carbonate, diethyl carbonate, propylene carbonate, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, and dioxolane.
[0041] The soaking time is 1 minute to 10 minutes;
[0042] The thickness of the formed sodium fluoride layer is 1 μm-50 μm, which can be any value within the above range, such as 1 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 40 μm, 45 μm, 50 μm, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable; when the thickness of the sodium fluoride layer is less than 1 μm, the waterproof effect and the effect of improving sodium deposition of the too thin sodium fluoride layer are not obvious; when the thickness of the sodium fluoride layer is greater than 50 μm, the too thick sodium fluoride layer will affect the transfer rate of sodium ions, and the thickness of the sodium fluoride layer is preferably 20 μm.
[0043] The composite negative electrode prepared by the above preparation method in the embodiment of the present invention can be assembled with a positive electrode, an electrolyte or a solid electrolyte, and a separator to form a sodium battery; wherein the separator includes but is not limited to any one of a polyethylene separator, a polypropylene separator, and a glass fiber separator.
[0044] The above-mentioned sodium battery includes: any one of a sodium ion battery, a sodium metal battery, and an all-solid-state sodium battery; wherein the sodium ion battery also includes an organic sodium ion battery or an aqueous sodium ion battery.
[0045] In order to better understand the technical solution provided by the present invention, the preparation process and characteristics of the composite negative electrode of the present invention are respectively described below with multiple specific examples.
[0046] Example 1
[0047] This embodiment provides a preparation process and performance test of a composite negative electrode, and the specific process is as follows:
[0048] (1) A block of metallic sodium with a purity of 99.7% was taken out from kerosene, cut into small pieces with a blade in a glove box filled with argon, and then rolled and cut into sodium sheets with a diameter of 12 mm and a thickness of 0.3 mm.
[0049] (2) A polytetrafluoroethylene film (PTFE) with a thickness of 0.02 mm was cut into films with a thickness of 16 mm using a slicer, and the cut polytetrafluoroethylene film was adhered to the surface of the sodium sheet by pressing in a glove box filled with argon gas to obtain a prefabricated negative electrode.
[0050] (3) The prefabricated negative electrode is immersed in an organic solvent, ethylene glycol dimethyl ether, for 2 minutes, so that the sodium in the catalytic sodium sheet reacts with the fluorine in the fluorine-containing high molecular polymer film to form a sodium fluoride layer, thereby obtaining a composite negative electrode, referred to as a PTFE-Na negative electrode.
[0051] The composite negative electrode prepared in this example was used to assemble a PTFE-Na / Cu half-cell, a PTFE-Na / PTFE-Na symmetrical cell, and a full cell and tested. The specific process is as follows:
[0052] Assembly of PTFE-Na / Cu half-cell: First, wash the cut copper sheet with dilute hydrochloric acid, then wash with a large amount of deionized water until neutral, and finally wash twice with alcohol and air-dry at room temperature; use the washed copper sheet as the counter electrode and add 1 mol / L NaPF 6 Ethylene glycol dimethyl ether solution was used as the electrolyte salt and polypropylene diaphragm was used as the separator in an argon glove box (H 2 O<0.01ppm,O 2 <0.01ppm), and assembled with the PTFE-Na negative electrode prepared by the present invention into a half-cell.
[0053] Assembly of PTFE-Na / PTFE-Na symmetric battery: Take two fluorinated sodium sheets PTFE-Na and mix them with 1 mol / L NaPF 6 Ethylene glycol dimethyl ether solution was used as the electrolyte salt and polypropylene diaphragm was used as the separator in an argon glove box (H 2 O<0.01ppm,O 2 <0.01ppm) were assembled into symmetrical cells.
[0054] Assembly of the full battery: First, prepare the positive electrode sheet. Prepare sodium vanadium phosphate, binder polyvinylidene fluoride and conductive agent acetylene black in a mass ratio of 90:3:7 to form a slurry, apply it on the washed aluminum foil with an applicator, dry it in an oven at 80°C for 8 hours, and then press it into a positive electrode sheet with a tablet press at 10MPa; the negative electrode sheet adopts the PTFE-Na negative electrode prepared in this example, and uses 1mol / L NaPF 6 Ethylene glycol dimethyl ether solution was used as the electrolyte salt and polypropylene diaphragm was used as the separator in an argon glove box (H 2 O<0.01ppm,O 2 <0.01ppm), assembled into a full battery.
[0055] The test process is as follows:
[0056] Test the coulombic efficiency of the PTFE-Na / Cu half-cell: first, activate the battery at a current density of 0.05C in the voltage range of 0.01V-1V, then perform charge and discharge tests at a current density of 1C, and calculate the coulombic efficiency of the half-cell by the ratio of discharge capacity to charge capacity.
[0057] Test the PTFE-Na / PTFE-Na symmetric battery: at 1mA / cm 2 Under the same current density, sodium ions are extracted and inserted, and the growth of sodium dendrites is judged by the overpotential. The overpotential is the result of the electrode potential being out of balance during the reaction. The higher the overpotential, the more sodium metal is deposited, which makes it easier to generate dendrites and cause a short circuit in the battery.
[0058] Test the cycle capacity retention rate of the whole battery: first activate the battery at 0.2C, then test it at 1C, with an operating voltage of 2.5V-3.7V (where the charging voltage is 3.7V and the discharge cut-off voltage is 2.5V). Perform charge and discharge tests on the battery to test the specific capacity retention rate of the whole battery after 200 cycles.
[0059] The test data of the three batteries assembled in this embodiment are detailed in Table 1.
[0060] Example 2
[0061] This embodiment provides a preparation process and performance test of a composite negative electrode, and the specific process is as follows:
[0062] (1) A block of metallic sodium with a purity of 99.7% was taken out from kerosene, cut into small pieces with a blade in a glove box filled with argon, and then rolled and cut into sodium sheets with a diameter of 12 mm and a thickness of 0.2 mm.
[0063] (2) A polychlorotrifluoroethylene (PCTFE) film with a thickness of 0.01 mm was cut into films with a thickness of 16 mm using a slicer, and the cut polytetrafluoroethylene film was adhered to the surface of the sodium sheet by pressing in a glove box filled with argon gas to obtain a prefabricated negative electrode.
[0064] (3) The prefabricated negative electrode is immersed in an organic solvent, diethylene glycol dimethyl ether, for 3 minutes, so that the sodium in the catalytic sodium sheet reacts with the fluorine in the PCTFE film to form a sodium fluoride layer, thereby obtaining a composite negative electrode, referred to as a PCTFE-Na negative electrode.
[0065] The composite negative electrode prepared in this example was used to assemble a PCTFE-Na / Cu half-cell, a PCTFE-Na / PCTFE-Na symmetrical cell, and a full cell and tested. The specific process is as follows:
[0066] Assembly of PCTFE-Na / Cu half-cell: First, wash the cut copper sheet with dilute hydrochloric acid, then wash with a large amount of deionized water until neutral, and finally wash twice with alcohol and air-dry at room temperature. Use the washed copper sheet as the counter electrode and add 1 mol / L NaPF 6 Ethylene glycol dimethyl ether solution was used as the electrolyte salt and polypropylene diaphragm was used as the separator in an argon glove box (H 2 O<0.01ppm,O 2 <0.01ppm), and assembled with the PCTFE-Na negative electrode prepared by the present invention into a half-cell.
[0067] Assembly of PCTFE-Na / PCTFE-Na symmetric battery: Take two fluorinated sodium sheets PCTFE-Na and add 1 mol / L NaPF 6 Ethylene glycol dimethyl ether solution was used as the electrolyte salt and polypropylene diaphragm was used as the separator in an argon glove box (H 2 O<0.01ppm,O 2 <0.01ppm) were assembled into symmetrical cells.
[0068] Assembly of the full battery: First, prepare the positive electrode sheet. Prepare sodium vanadium phosphate, binder polyvinylidene fluoride and conductive agent acetylene black in a mass ratio of 90:3:7 to form a slurry, apply it on the washed aluminum foil with an applicator, dry it in an oven at 80°C for 8 hours, and then press it into a positive electrode sheet with a tablet press at 10MPa; the negative electrode sheet adopts the PCTFE-Na negative electrode prepared in this example, and uses 1mol / L NaPF 6 Ethylene glycol dimethyl ether solution was used as the electrolyte salt and polypropylene diaphragm was used as the separator in an argon glove box (H 2 O<0.01ppm,O 2 <0.01ppm), assembled into a full battery.
[0069] The test process of the three batteries assembled in this embodiment is the same as that in Embodiment 1. The test data are detailed in Table 1.
[0070] Example 3
[0071] This embodiment provides a preparation process and performance test of a composite negative electrode, and the specific process is as follows:
[0072] (1) A block of metallic sodium with a purity of 99.7% was taken out from kerosene, cut into small pieces with a blade in a glove box filled with argon, and then rolled and cut into sodium sheets with a diameter of 12 mm and a thickness of 0.5 mm.
[0073] (2) A perfluoroalkoxy resin (PFA) film with a thickness of 0.03 mm was cut into films with a thickness of 16 mm using a slicer, and the cut polytetrafluoroethylene film was adhered to the surface of the sodium sheet by pressing in a glove box filled with argon gas to obtain a prefabricated negative electrode.
[0074] (3) The prefabricated negative electrode is immersed in an organic solvent, tetraethylene glycol dimethyl ether, for 2 minutes, so that the sodium in the catalytic sodium sheet reacts with the fluorine in the PFA film to form a sodium fluoride layer, thereby obtaining a composite negative electrode, referred to as a PFA-Na negative electrode.
[0075] The composite negative electrode prepared in this embodiment was used to assemble a PFA-Na / Cu half-cell, a PFA-Na / PFA-Na symmetrical cell, and a full cell and tested. The specific process is as follows:
[0076] Assembly of PFA-Na / Cu half-cell: First, wash the cut copper sheet with dilute hydrochloric acid, then wash with a large amount of deionized water until neutral, and finally wash twice with alcohol and air-dry at room temperature. Use the washed copper sheet as the counter electrode and add 1 mol / L NaPF 6 Ethylene glycol dimethyl ether solution was used as the electrolyte salt and polypropylene diaphragm was used as the separator in an argon glove box (H 2 O<0.01ppm,O 2 <0.01ppm), and assembled with the PFA-Na negative electrode prepared by the present invention into a half-cell.
[0077] Assembly of PFA-Na / PFA-Na symmetric battery: Take two fluorinated sodium sheets PFA-Na and add 1 mol / L NaPF 6 Ethylene glycol dimethyl ether solution was used as the electrolyte salt and polypropylene diaphragm was used as the separator in an argon glove box (H 2 O<0.01ppm,O 2 <0.01ppm) were assembled into symmetrical cells.
[0078] Assembly of the full battery: First, prepare the positive electrode sheet. Prepare sodium vanadium phosphate, binder polyvinylidene fluoride and conductive agent acetylene black in a mass ratio of 90:3:7 to form a slurry, apply it on the washed aluminum foil with an applicator, dry it in an oven at 80°C for 8 hours, and then press it into a positive electrode sheet with a tablet press at 10MPa; the negative electrode sheet adopts the PFA-Na negative electrode prepared in this example, and uses 1 mol / L NaPF 6 Ethylene glycol dimethyl ether solution was used as the electrolyte salt and polypropylene diaphragm was used as the separator in an argon glove box (H 2 O<0.01ppm,O 2 <0.01ppm), assembled into a full battery.
[0079] The test process of the three batteries assembled in this embodiment is the same as that in Embodiment 1. The test data are detailed in Table 1.
[0080] Example 4
[0081] This embodiment provides a preparation process and performance test of a composite negative electrode, and the specific process is as follows:
[0082] (1) A block of metallic sodium with a purity of 99.7% was taken out from kerosene, cut into small pieces with a blade in a glove box filled with argon, and then rolled and cut into sodium sheets with a diameter of 12 mm and a thickness of 0.4 mm.
[0083] (2) A polytetrafluoroethylene film (FEP) with a thickness of 0.05 mm was cut into films with a thickness of 16 mm using a slicer, and the cut polytetrafluoroethylene film was adhered to the surface of the sodium sheet by pressing in a glove box filled with argon gas to obtain a prefabricated negative electrode.
[0084] (3) The prefabricated negative electrode is immersed in an organic solvent, diethylene glycol, for 2 minutes, so that the sodium in the catalytic sodium sheet reacts with the fluorine in the FEP film to form a sodium fluoride layer, thereby obtaining a composite negative electrode, referred to as FEP-Na negative electrode.
[0085] The composite negative electrode prepared in this example was used to assemble a FEP-Na / Cu half-cell, a FEP-Na / FEP-Na symmetrical cell, and a full cell and tested. The specific process is as follows:
[0086] Assembly of FEP-Na / Cu half-cell: First, wash the cut copper sheet with dilute hydrochloric acid, then wash with a large amount of deionized water until neutral, and finally wash twice with alcohol and air-dry at room temperature. Use the washed copper sheet as the counter electrode and add 1 mol / L NaPF 6 Ethylene glycol dimethyl ether solution was used as the electrolyte salt and polypropylene diaphragm was used as the separator in an argon glove box (H 2 O<0.01ppm,O 2 <0.01ppm), and assembled with the FEP-Na negative electrode prepared by the present invention into a half-cell.
[0087] Assembly of FEP-Na / FEP-Na symmetrical battery: Take two fluorinated sodium sheets FEP-Na and add 1 mol / L NaPF 6 Ethylene glycol dimethyl ether solution was used as the electrolyte salt and polypropylene diaphragm was used as the separator in an argon glove box (H 2 O<0.01ppm,O 2 <0.01ppm) were assembled into symmetrical cells.
[0088] Assembly of the full battery: First, prepare the positive electrode sheet. Prepare sodium vanadium phosphate, binder polyvinylidene fluoride and conductive agent acetylene black in a mass ratio of 90:3:7 to form a slurry, apply it on the washed aluminum foil with an applicator, dry it in an oven at 80°C for 8 hours, and then press it into a positive electrode sheet with a tablet press at 10MPa; the negative electrode sheet adopts the FEP-Na negative electrode prepared in this example, and uses 1mol / L NaPF 6 Ethylene glycol dimethyl ether solution was used as the electrolyte salt and polypropylene diaphragm was used as the separator in an argon glove box (H 2 O<0.01ppm,O 2 <0.01ppm), assembled into a full battery.
[0089] The test process of the three batteries assembled in this embodiment is the same as that in Embodiment 1. The test data are detailed in Table 1.
[0090] Example 5
[0091] This embodiment provides a preparation process and performance test of a composite negative electrode, and the specific process is as follows:
[0092] (1) A block of metallic sodium with a purity of 99.7% was taken out from kerosene, cut into small pieces with a blade in a glove box filled with argon, and then rolled and cut into sodium sheets with a diameter of 12 mm and a thickness of 0.7 mm.
[0093] (2) A polyvinyl fluoride (PVF) film with a thickness of 0.08 mm was cut into films with a thickness of 16 mm using a slicer, and the cut polytetrafluoroethylene film was adhered to the surface of the sodium sheet by pressing in a glove box filled with argon gas to obtain a prefabricated negative electrode.
[0094] (3) The prefabricated negative electrode is immersed in an organic solvent, triethylene glycol di-2-ethylhexanoate, for 5 minutes, so that the sodium in the catalytic sodium sheet reacts with the fluorine in the PVF film to form a sodium fluoride layer, thereby obtaining a composite negative electrode, referred to as a PVF-Na negative electrode.
[0095] The composite negative electrode prepared in this embodiment is used to assemble a PVF-Na / Cu half-cell, a PVF-Na / PVF-Na symmetrical cell, and a full cell and tested. The specific process is as follows:
[0096] Assembly of PVF-Na / Cu half-cell: First, wash the cut copper sheet with dilute hydrochloric acid, then wash with a large amount of deionized water until neutral, and finally wash twice with alcohol and air-dry at room temperature. Use the washed copper sheet as the counter electrode and add 1 mol / L NaPF 6 Ethylene glycol dimethyl ether solution was used as the electrolyte salt and polypropylene diaphragm was used as the separator in an argon glove box (H 2 O<0.01ppm,O 2<0.01ppm), and assembled with the PVF-Na negative electrode prepared by the present invention into a half-cell.
[0097] Assembly of PVF-Na / PVF-Na symmetrical battery: Take two fluorinated sodium sheets PVF-Na and add 1 mol / L NaPF 6 Ethylene glycol dimethyl ether solution was used as the electrolyte salt and polypropylene diaphragm was used as the separator in an argon glove box (H 2 O<0.01ppm,O 2 <0.01ppm) were assembled into symmetrical cells.
[0098] Assembly of the full battery: First, prepare the positive electrode sheet. Prepare sodium vanadium phosphate, binder polyvinylidene fluoride and conductive agent acetylene black in a mass ratio of 90:3:7 to form a slurry, apply it on the washed aluminum foil with an applicator, dry it in an oven at 80°C for 8 hours, and then press it into a positive electrode sheet with a tablet press at 10MPa; the negative electrode sheet adopts the PVF-Na negative electrode prepared in this example, and uses 1mol / L NaPF 6 Ethylene glycol dimethyl ether solution was used as the electrolyte salt and polypropylene diaphragm was used as the separator in an argon glove box (H 2 O<0.01ppm,O 2 <0.01ppm), assembled into a full battery.
[0099] The test process of the three batteries assembled in this embodiment is the same as that in Embodiment 1. The test data are detailed in Table 1.
[0100] Example 6
[0101] This embodiment provides a preparation process and performance test of a composite negative electrode, and the specific process is as follows:
[0102] (1) A block of metallic sodium with a purity of 99.7% was taken out from kerosene, cut into small pieces with a blade in a glove box filled with argon, and then rolled and cut into sodium sheets with a diameter of 12 mm and a thickness of 0.9 mm.
[0103] (2) A 0.1 mm thick polytetrafluoroethylene (PVF) film was cut into 16 mm films using a slicer, and the cut polytetrafluoroethylene film was adhered to the surface of the sodium sheet by pressing in a glove box filled with argon gas to obtain a prefabricated negative electrode.
[0104] (3) The prefabricated negative electrode is immersed in an organic solvent, ethylene glycol dimethyl ether, for 6 minutes, so that the sodium in the catalytic sodium sheet reacts with the fluorine in the PVF film to form a sodium fluoride layer, thereby obtaining a composite negative electrode, referred to as a PVF-Na negative electrode.
[0105] The composite negative electrode prepared in this embodiment is used to assemble a PVF-Na / Cu half-cell, a PVF-Na / PVF-Na symmetrical cell, and a full cell and tested. The specific process is as follows:
[0106] Assembly of PVF-Na / Cu half-cell: First, wash the cut copper sheet with dilute hydrochloric acid, then wash with a large amount of deionized water until neutral, and finally wash twice with alcohol and air-dry at room temperature. Use the washed copper sheet as the counter electrode and add 1 mol / L NaPF 6 Ethylene glycol dimethyl ether solution was used as the electrolyte salt and polypropylene diaphragm was used as the separator in an argon glove box (H 2 O<0.01ppm,O 2 <0.01ppm) and the PVF-Na negative electrode prepared by the present invention are assembled into a half-cell.
[0107] Assembly of PVF-Na / PVF-Na symmetrical battery: Take two fluorinated sodium sheets PVF-Na and add 1 mol / L NaPF 6 Ethylene glycol dimethyl ether solution was used as the electrolyte salt and polypropylene diaphragm was used as the separator in an argon glove box (H 2 O<0.01ppm,O 2 <0.01ppm) were assembled into symmetrical cells.
[0108] Assembly of the full battery: First, prepare the positive electrode sheet. Prepare sodium vanadium phosphate, binder polyvinylidene fluoride and conductive agent acetylene black in a mass ratio of 90:3:7 to form a slurry, apply it on the washed aluminum foil with an applicator, dry it in an oven at 80°C for 8 hours, and then press it into a positive electrode sheet with a tablet press at 10MPa; the negative electrode sheet adopts the PVF-Na negative electrode prepared in this example, and uses 1mol / L NaPF 6 Ethylene glycol dimethyl ether solution was used as the electrolyte salt and polypropylene diaphragm was used as the separator in an argon glove box (H 2 O<0.01ppm,O 2 <0.01ppm), assembled into a full battery.
[0109] The test process of the three batteries assembled in this embodiment is the same as that in Embodiment 1. The test data are detailed in Table 1.
[0110] Example 7
[0111] This embodiment provides a preparation process and performance test of a composite negative electrode, and the specific process is as follows:
[0112] (1) A block of metallic sodium with a purity of 99.7% was taken out from kerosene, cut into small pieces with a blade in a glove box filled with argon, and then rolled and cut into sodium sheets with a diameter of 12 mm and a thickness of 1.0 mm.
[0113] (2) A 0.12 mm thick ethylene-tetrafluoroethylene copolymer (ETFE) was cut into 16 mm thin films using a slicer, and the cut polytetrafluoroethylene film was adhered to the surface of the sodium sheet by pressing in a glove box filled with argon gas to obtain a prefabricated negative electrode.
[0114] (3) The prefabricated negative electrode is immersed in an organic solvent of dioxane for 6 minutes, and the sodium in the catalytic sodium sheet reacts with the fluorine in the ETFE film to form a sodium fluoride layer, thereby obtaining a composite negative electrode, referred to as ETFE-Na negative electrode.
[0115] The composite negative electrode prepared in this embodiment is used to assemble ETFE-Na / Cu half-cell, ETFE-Na / ETFE-Na symmetrical cell, and full cell and tested. The specific process is as follows:
[0116] Assembly of ETFE-Na / Cu half-cell: First, wash the cut copper sheet with dilute hydrochloric acid, then wash with a large amount of deionized water until neutral, and finally wash twice with alcohol and air-dry at room temperature. Use the washed copper sheet as the counter electrode and add 1 mol / L NaPF 6 Ethylene glycol dimethyl ether solution was used as the electrolyte salt and polypropylene diaphragm was used as the separator in an argon glove box (H 2 O<0.01ppm,O 2 <0.01ppm), and assembled with the ETFE-Na negative electrode prepared by the present invention into a half-cell.
[0117] Assembly of ETFE-Na / ETFE-Na symmetric battery: Take two fluorinated sodium sheets ETFE-Na and add 1 mol / L NaPF 6 Ethylene glycol dimethyl ether solution was used as the electrolyte salt and polypropylene diaphragm was used as the separator in an argon glove box (H 2 O<0.01ppm,O 2 <0.01ppm) were assembled into symmetrical cells.
[0118] Assembly of the full battery: First, prepare the positive electrode sheet. Prepare sodium vanadium phosphate, binder polyvinylidene fluoride and conductive agent acetylene black in a mass ratio of 90:3:7 to form a slurry, apply it on the washed aluminum foil with an applicator, dry it in an oven at 80°C for 8 hours, and then press it into a positive electrode sheet with a tablet press at 10MPa; the negative electrode sheet adopts the ETFE-Na negative electrode prepared in this example, and uses 1 mol / L NaPF 6 Ethylene glycol dimethyl ether solution was used as the electrolyte salt and polypropylene diaphragm was used as the separator in an argon glove box (H 2 O<0.01ppm,O 2 <0.01ppm), assembled into a full battery.
[0119] The test process of the three batteries assembled in this embodiment is the same as that in Embodiment 1. The test data are detailed in Table 1.
[0120] Example 8
[0121] This embodiment provides a preparation process and performance test of a composite negative electrode, and the specific process is as follows:
[0122] (1) A block of metallic sodium with a purity of 99.7% was taken out from kerosene, cut into small pieces with a blade in a glove box filled with argon, and then rolled and cut into sodium sheets with a diameter of 12 mm and a thickness of 0.5 mm.
[0123] (2) A polytetrafluoroethylene film (PTFE) with a thickness of 0.15 mm was cut into films with a thickness of 16 mm using a slicer, and the cut polytetrafluoroethylene film was adhered to the surface of the sodium sheet by pressing in a glove box filled with argon gas to obtain a prefabricated negative electrode.
[0124] (3) The prefabricated negative electrode is immersed in an organic solvent, tetraethylene glycol dimethyl ether, for 4 minutes, so that the sodium in the catalytic sodium sheet reacts with the fluorine in the PTFE film to form a sodium fluoride layer, thereby obtaining a composite negative electrode, referred to as a PTFE-Na negative electrode.
[0125] The composite negative electrode prepared in this example was used to assemble a PTFE-Na / Cu half-cell, a PTFE-Na / PTFE-Na symmetrical cell, and a full cell and tested. The specific process is as follows:
[0126] Assembly of PTFE-Na / Cu half-cell: First, wash the cut copper sheet with dilute hydrochloric acid, then wash with a large amount of deionized water until neutral, and finally wash twice with alcohol and air-dry at room temperature; use the washed copper sheet as the counter electrode and add 1 mol / L NaPF 6 Ethylene glycol dimethyl ether solution was used as the electrolyte salt and polypropylene diaphragm was used as the separator in an argon glove box (H 2 O<0.01ppm,O 2 <0.01ppm), and assembled with the PTFE-Na negative electrode prepared by the present invention into a half-cell.
[0127] Assembly of PTFE-Na / PTFE-Na symmetric battery: Take two fluorinated sodium sheets PTFE-Na and add 1 mol / L NaPF 6 Ethylene glycol dimethyl ether solution was used as the electrolyte salt and polypropylene diaphragm was used as the separator in an argon glove box (H 2 O<0.01ppm,O 2 <0.01ppm) were assembled into symmetrical cells.
[0128] Assembly of the full battery: First, prepare the positive electrode sheet. Prepare sodium vanadium phosphate, binder polyvinylidene fluoride and conductive agent acetylene black in a mass ratio of 90:3:7 to form a slurry, apply it on the washed aluminum foil with an applicator, dry it in an oven at 80°C for 8 hours, and then press it into a positive electrode sheet with a tablet press at 10MPa; the negative electrode sheet adopts the PTFE-Na negative electrode prepared in this example, and uses 1mol / L NaPF 6 Ethylene glycol dimethyl ether solution was used as the electrolyte salt and polypropylene diaphragm was used as the separator in an argon glove box (H 2 O<0.01ppm,O 2 <0.01ppm), assembled into a full battery.
[0129] The test process of the three batteries assembled in this embodiment is the same as that in Embodiment 1. The test data are detailed in Table 1.
[0130] In order to better illustrate the effect of the embodiment of the present invention, comparative example 1 is compared with the embodiment.
[0131] Comparative Example 1
[0132] This comparative example is different from the example in that the sodium sheet prepared in step (1) of Example 1 is directly used to assemble a Na / Cu half-cell, a Na / Na symmetric cell and a full cell and test them. The assembly process and test process of the three batteries are the same as those in Example 1. The test data are detailed in Table 1.
[0133] Table 1 summarizes the test data of three batteries assembled in Examples 1-8 and Comparative Example 1:
[0134]
[0135]
[0136] Table 1
[0137] By comparing the data in Table 1, it can be seen that the coulombic efficiency of the half-cell, the stability of the symmetrical cell and the capacity retention rate of the full cell of Examples 1-8 are all higher than those of Comparative Example 1. The reason is that in Comparative Example 1, the battery directly assembled with sodium metal sheets has uneven sodium ion deposition, and the highly reactive sodium reacts with the organic electrolyte to generate an unstable solid electrolyte membrane (SEI), resulting in the growth of sodium dendrites. The continuous growth of sodium dendrites during the cycle will greatly affect the stability of the battery, causing problems such as battery failure, and the loss of electrochemically active sodium will cause battery capacity loss. Therefore, the performance of the three batteries assembled in Comparative Example 1 is inferior to that of Examples 1-8. In Examples 1-8 of the present invention, the three batteries assembled with composite negative electrodes, the sodium fluoride layer in the composite negative electrode can effectively block the corrosion of water on the sodium metal sheet, and at the same time can inhibit the reaction of sodium with the organic electrolyte to generate an unstable solid electrolyte membrane (SEI) to cause the growth of sodium dendrites, reduce the capacity loss of the battery, achieve rapid transfer and uniform deposition of sodium ions, and improve the coulombic efficiency and cycle performance of the sodium battery.
[0138] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A composite negative electrode for a sodium battery, characterized in that: The composite negative electrode comprises: a sodium sheet, a sodium fluoride layer formed in situ on the surface of the sodium sheet, and a fluorine-containing high molecular polymer film; The sodium fluoride layer is formed by reacting a sodium sheet having a fluorine-containing polymer film attached to its surface under the catalysis of an organic solvent; The organic solvent includes esters and / or ethers.
2. The composite negative electrode according to claim 1, characterized in that The thickness of the fluorine-containing polymer film is 0.01mm-0.2mm; the fluorine-containing polymer in the fluorine-containing polymer film includes: one or more of polytetrafluoroethylene (PTFE), polychlorotrifluoroethylene (PCTFE), perfluoroalkoxy resin (PFA), polyperfluoroethylene propylene (FEP), ethylene-tetrafluoroethylene copolymer (ETFE), and polyvinyl fluoride (PVF).
3. The composite negative electrode according to claim 1, characterized in that: The thickness of the sodium sheet is 0.1mm-1mm; The organic solvent includes: one or more of diethylene glycol, triethylene glycol di-2-ethylhexanoate, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, and dioxolane.
4. The composite negative electrode according to claim 1, characterized in that: The thickness of the sodium fluoride layer is 1 μm-50 μm.
5. A method for preparing the composite negative electrode according to any one of claims 1 to 4, characterized in that: The preparation method comprises: The bulk sodium metal was cut into small pieces in a glove box filled with argon, rolled and then cut into sodium sheets; In a glove box, a fluorine-containing polymer film is placed on the surface of a sodium sheet, and the fluorine-containing polymer film is adhered to the surface of the sodium sheet by applying pressure to obtain a prefabricated negative electrode; The prefabricated negative electrode is immersed in an organic solvent to make the sodium in the sodium sheet react with the fluorine in the fluorine-containing high molecular polymer film to form a sodium fluoride layer, thereby obtaining a composite negative electrode.
6. The preparation method according to claim 5, characterized in that: The thickness of the fluorine-containing polymer film is 0.01 mm-0.2 mm; the fluorine-containing polymer in the fluorine-containing polymer film includes one or more of polytetrafluoroethylene (PTFE), polychlorotrifluoroethylene (PCTFE), perfluoroalkoxy resin (PFA), polyperfluoroethylene propylene (FEP), ethylene-tetrafluoroethylene copolymer (ETFE), and polyvinyl fluoride (PVF); The thickness of the sodium sheet is 0.1mm-1mm; The organic solvent includes esters and / or ethers.
7. The preparation method according to claim 5, characterized in that: The organic solvent includes: one or more of diethylene glycol, triethylene glycol di-2-ethylhexanoate, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, and dioxolane.
8. The preparation method according to claim 5, characterized in that: The soaking time is 1 minute to 10 minutes.
9. A sodium battery, characterized in that: The sodium battery comprises a positive electrode, a composite negative electrode as described in any one of claims 1 to 4, an electrolyte or a solid electrolyte, and a separator.
10. The sodium battery according to claim 9, characterized in that: The sodium battery includes any one of a sodium ion battery, a sodium metal battery, and an all-solid-state sodium battery.
Citation Information
Patent Citations
Sodium metal negative electrode protective layer, sodium metal negative electrode and preparation method and application thereof
CN112531145A
Alkali metal negative electrode composite protective film and preparation method thereof, alkali metal negative electrode and alkali metal secondary battery
CN112531165A
Fluoride composite solid electrolyte membrane and preparation method thereof, and solid sodium battery using fluoride composite solid electrolyte membrane
CN115000499A
Organic electroluminescent element, organic electroluminescent device and electronic device
JP2019080027A
All-solid-state polymer electrolyte, and preparation and application thereof
WO2016127786A1